Model Penyiapan Tenaga Terampil Kejuruan Melalui Implementasi Sistem Ganda: Kasus PT Siemens Indonesia - Ivan Hanafi (Universitas Negeri Malang, 2016)
The dual system has many forms of implementation, one of which the industry serves as educational establishment as well as a place for apprenticeship. The objective of this tudy was to examine the educational model of the dual system planned by PT Siemens Indonesia in preparing skilled workers in technical vocation. This model follows the Duale Ausbildungsystem developed in Germany with the content of the curriculum focuses more on practical components as compared to the theoritical part.